GANGGUAN BERBAHASA PSIKOGENIK LATAH PADA GRUP CAP TAWA DALAM ACARA BROWNIS TRANS TV: TINJAUAN PSIKOLINGUISTIK - Hermawan, Dimas; Ginanjar, Agi Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Cap Tawa is a comedy group consisting of three talkative middle-aged man, namely Deddy, Bayu, and Gary Iskak. In the realm of psycholinguistics, talkative is classified as one of the psychogenic language disorders. This research purposed to investigate the psychogenic language disorder of talkative in the Cap Tawa group on the Brownis Trans TV"™s program. This research uses qualitative method with a case study approach. Meanwhile, the data collection technique uses documentation technique. Next, the data analysis technique uses typology technique. The results and discussion of research show the psychogenic language disorder of talkative in the Cap Tawa group on the Brownis Trans TV"™s program based on types, among others: 1) Talkative echolalia with 5 behaviors, 2) Talkative echopraxia with 10 behaviors, 3) Talkative coprolalia with 10 behaviors, 4) Talkative auto echolalia with 15 behaviors, and 5) Talkative automatic obedience with 5 behaviors. Furthermore, this research hoped to provide benefits in the field of psycholinguistics, either theoretically or practically.